LPGL: Low-power graphics library for mobile AR headsets - CHOI Jaewon (Institutional Knowledge at Singapore Management University, 2019)
We present LpGL, an OpenGL API compatible Low-power Graphics Library for energy efficient AR headset applications. We first characterize the power consumption patterns of a state of the art AR headset, Magic Leap One, and empirically show that its internal GPU is the most impactful and controllable energy consumer. Based on the preliminary studies, we design LpGL so that it uses the device's gaze/head orientation information and geometry data to infer user perception information, intercepts application-level graphics API calls, and employs frame rate control, mesh simplification, and culling techniques to enhance energy efficiency of AR headsets without detriment of user experience. Results from a comprehen- sive set of controlled in-lab experiments and an IRB-approved user study with 25 participants show that LpGL reduces up to 22% of total energy usage while adding only 46 sec of latency per object with close to no loss in subjective user experience.